PERBANDINGAN PARADIGMA KEILMUAN DALAM FILSAFAT ILMU ISLAM DAN BARAT SERTA IMPLIKASINYA : COMPARISON OF SCIENTIFIC PARADIGMS IN ISLAMIC AND WESTERN PHILOSOPHY OF SCIENCE AND ITS IMPLICATIONS - Meily Nurdiyansyah, Nana; Arief, Armai; Widya Pratiwi, Sabrina; Ayu Savira, Litha; Pamungkas, Fauzan; Lesmana Dwi Putra, Rangga (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2025)
This research was a literature study that employed a qualitative descriptive approach to illustrate the philosophical underpinnings of Islamic and Western scientific thought. The study aimed to examine and compare the paradigms of scientific philosophy in Islam and the West. The authors analyzed primary and secondary literature sources, including books, articles, and journals, that were relevant to the study. The findings indicate that Islamic scientific philosophy integrates revelation, reason, and intuition with an orientation toward spiritual values, whereas Western scientific philosophy relies on reason, logic, and empiricism with a pragmatic and secular tendency. This fundamental difference affects curriculum design, teaching methods, and the characteristics of graduates. Therefore, a deep understanding of both paradigms is essential to formulate an educational system that is integrated, contextual, and relevant to the needs of the times without forsaking spiritual values.